Proceedings of the 7th International Conference and Exhibition on Sustainable Energy and Advanced Materials (ICE-SEAM 2021), Melaka, Malaysia - Abdollah, Mohd Fadzli Bin.; Amiruddin, Hilmi; Phuman Singh, Amrik Singh; Abdul Munir, Fudhail; Ibrahim, Asriana; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book gathers the proceedings of the 7th International Conference and Exhibition on Sustainable Energy and Advanced Materials (ICE-SEAM), held on November 2021, a virtual conference organized in Melaka, Malaysia. It focuses on two relatively broad areas$1 (Badvanced materials and sustainable energy$1 (Band a diverse range of subtopics: Advanced materials and related technologies: liquid crystals, semiconductors, superconductors, optics, lasers, sensors, mesoporous materials, nanomaterials, smart ferrous materials, amorphous materials, crystalline materials, biomaterials, metamaterials, composites, polymers, design, analysis, development, manufacturing, processing and testing for advanced materials. Sustainable energy and related technologies: energy management, storage, conservation, industrial energy efficiency, energy-efficient buildings, energy-efficient traffic systems, energy distribution, energy modeling, hybrid and integrated energy systems, fossil energy, nuclear energy, bioenergy, biogas, biomass geothermal power, non-fossil energies, wind energy, hydropower, solar photovoltaic, fuel cells, electrification, and electrical power systems and controls.s
Design and Development of Filament Extruder for 3D Printing Machine -- Application of GaBi Software in Identifying Potential Environmental Impacts in Fabrication of 3D Bone Tissue Engineering -- Multi-Objective Optimization of 3D-Printed ABS Using Response Surface Methodology.
Keywords: Electric power distribution; Materials; Catalysis; Force and energy; Energy Grids and Networks; Materials for Energy and Catalysis; Materials Engineering; Materials -- Congresses; Renewable energy sources -- Congresses; Sustainable development -- Congresses